Critical and Scientific Thinking Assessment in Preservice Teachers at a Chilean University - Ossa-Cornejo, Carlos (2018)
This paper describes a research project focused on identifying student-teachers’ critical thinking performance levels in scientific reasoning and, secondly, on analyzing the reliability level of the Critical Thinking Tasks test (CTT). As part of the methodology, a non-probabilistic sample of 129 teacher education students from different majors at Bio-Bio University was considered, and the Critical Thinking Task test was applied to collect data. The data analysis was conducted using descriptive statistics, reliability measures and mean score differences. The data showed that the instrument is reliable (α=0,79); there is also a relatively low performance in the global test and its dimensions; and there are differences between the different teacher education programs. It is concluded that the instrument is reliable, and findings support the idea that knowledge-based areas influence critical thinking. Finally, it is necessary to strengthen specific sub-skills to enhance critical thinking as a contribution for scientific reasoning.